Information on the piloting of the curriculum in technology education for primary and secondary schools in the CARICOM - Gift, Edrick (CCS GeorgetownGY)
Presents the rationale for the programme; the content of the curriculum; the purpose of piloting it; what of the pilot entails; and, finally the piloting of the curriculum at the primary and secondary levels.